The metastasis inducer CCN1 (CYR61) activates the fatty acid synthase (FASN)-driven lipogenic phenotype in breast cancer cells - Menendez, Javier A. (2016)
The angiogenic inducer CCN1 (Cysteine-rich 61, CYR61) is differentially activated in metastatic breast carcinomas. However, little is known about the precise mechanisms that underlie the pro-metastatic actions of CCN1. Here, we investigated the impact of CCN1 expression on fatty acid synthase (FASN), a metabolic oncogene thought to provide cancer cells with proliferative and survival advantages. Forced expression of CCN1 in MCF-7 cells robustly up-regulated FASN protein expression and also significantly increased FASN gene promoter activity 2- to 3-fold, whereas deletion of the sterol response element-binding protein (SREBP) binding site in the FASN promoter completely abrogated CCN1-driven transcriptional activation. Pharmacological blockade of MAPK or PI-3´K activation similarly prevented the ability of CCN1 to induce FASN gene activation. Pharmacological inhibition of FASN activity with the mycotoxin cerulenin or the small compound C75 reversed CCN1-induced acquisition of estrogen independence and resistance to hormone therapies such as tamoxifen and fulvestrant in anchorage-independent growth assays. This study uncovers FASNdependent endogenous lipogenesis as a new mechanism controlling the metastatic phenotype promoted by CCN1. Because estrogen independence and progression to a metastatic phenotype are hallmarks of therapeutic resistance and mortality in breast cancer, this previously unrecognized CCN1-driven lipogenic phenotype represents a novel metabolic target to clinically manage metastatic disease progression.